2019
DOI: 10.1016/j.chemosphere.2019.05.280
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites of phosphate flame retardants and alternative plasticizers in urine from intensive care patients

Abstract: Several regulatory offices called for the phase-out of di (2-ethylhexyl) phthalate (DEHP) in medical devices if safer alternatives are available. In medical devices, the occurrence of alternative plasticizers (APs) is widely variable among types of devices. However, plasticizer use is constantly evolving, as there is no reference to guide manufacturers in the choice and amount to be integrated into their products.As intensive care unit (ICU) patients need numerous indwelling plastic devices during their treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 31 publications
(55 reference statements)
1
13
0
Order By: Relevance
“…Numerous studies have demonstrated that dialkyl phosphate (DAP) metabolites of OPEs such as DPHP can serve as the primary biomarkers of OPEs such as TPHP in OPE-exposed humans, given that DAPs were frequently detected in human samples. ,− Two DAPs, namely, 2-ethylhexyl phenyl hydrogen phosphate (EHPHP) and bis-(2-ethylhexyl)hydrogen phosphate (DEHP), have been detected in human blood and/or urine samples. , These two DAPs were generally regarded as potential biomarkers of human exposure to EHDPP and TEHP, respectively. However, the first detection of BEHPP in our present study indicates that EHPHP and DEHP will be no longer specific metabolites for EHDPP and TEHP as these two metabolites could also be derived from BEHPP biotransformation.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have demonstrated that dialkyl phosphate (DAP) metabolites of OPEs such as DPHP can serve as the primary biomarkers of OPEs such as TPHP in OPE-exposed humans, given that DAPs were frequently detected in human samples. ,− Two DAPs, namely, 2-ethylhexyl phenyl hydrogen phosphate (EHPHP) and bis-(2-ethylhexyl)hydrogen phosphate (DEHP), have been detected in human blood and/or urine samples. , These two DAPs were generally regarded as potential biomarkers of human exposure to EHDPP and TEHP, respectively. However, the first detection of BEHPP in our present study indicates that EHPHP and DEHP will be no longer specific metabolites for EHDPP and TEHP as these two metabolites could also be derived from BEHPP biotransformation.…”
Section: Resultsmentioning
confidence: 99%
“…Widespread existence of OPFRs in the environment raises alarming concerns on its environmental toxicity and human health hazards. In this regard, bioaccumulated TCEP was found in human fat and detected in body fluids, signifying grave health concerns [7,11]. Some in vitro and in vivo test models have affirmed liver toxicity due to TCEP exposure, and they categorized TCEP as a carcinogenic chemical [13, 14,17].…”
Section: Discussionmentioning
confidence: 99%
“…A biomonitoring study on 323 individuals in China from different age groups showed the presence of TCEP and its metabolites in urine, leading to calculated exposure limits of TCEP from 96.9 to 46,700 (equivalent to 52.2-25,200) ng/kg bw/d [10]. Within the healthcare environment, intensive care unit patients subjected to treatment with specific medical devices have also exhibited urinary presence of TCEP [11]. Not only are humans at risks of TCEP exposure; rather, a recent environmental study also categorized TCEP as the most frequently detected OPFR in the bays of China and Japan [12].…”
Section: Introductionmentioning
confidence: 99%
“…DINCH has been shown to leach from PVC in amounts half those for DEHP (Haishima et al, 2014), urinary DiDP metabolites increased after cardiac surgery (Shang et al, 2019), and low levels of TOTM metabolites have been detected in blood of infants after cardiac surgery (Eckert et al, 2020). Quantification of DEHA, DEHTP, DINCH, and DPHP metabolites in urine of adult ICU patients revealed detectable quantities of almost all metabolites, whereas many were not detected in control samples (Bastiaensen et al, 2019). Detection frequencies in the patients were low, but sampling took place before the increase in the use of alternative plasticizers.…”
Section: Discussionmentioning
confidence: 99%